Acalabrutinib, a second-generation Bruton’s tyrosine kinase inhibitor - Kriegsmann, Katharina; Kriegsmann, Mark; Witzens-Harig, Mathias (Small molecules in hematology, 2018)
The Bruton’s tyrosine kinase (BTK) is an essential in the B-cell receptor (BCR) signaling pathway which was identified as crucial in the pathogenesis of B-cell malignancies. Ibrutinib, a first-in-class BTK inhibitor, has been approved for the treatment of distinct B-cell malignancies. To overcome off-target side effects of and emerging resistances to ibrutinib, more selective second-generation BTK inhibitors were developed. Acalabrutinib is a novel second-generation BTK inhibitor and has shown promising safety and efficacy profiles in phase 1/2 clinical trials in patients with relapsed CLL and pretreated MCL. Recently, acalabrutinib was approved by the FDA for treatment of adult patients with MCL who received at least one prior therapy. However, clinical trials on a direct comparison between ibrutinib and acalabrutinib and on combination treatment options with other agents as CD20 antibodies are warranted.
Gesehen am 29.10.2019